2023
DOI: 10.1038/s41598-023-39735-w
|View full text |Cite
|
Sign up to set email alerts
|

Depression in healthcare workers during COVID-19 pandemic: results from Czech arm of HEROES Study

Abstract: The pandemic due to COVID-19 brought new risks for depression of health care workers, which may have differently influenced men and women. We aimed to investigate (1) whether health care workers in Czechia experienced an increase in depression during the COVID-19 pandemic, (2) which factors contributed the most to this change, and (3) whether the magnitude of the associations differed by gender. We studied 2564 participants of the Czech arm of the international COVID-19 HEalth caRe wOrkErS (HEROES) Study. Onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Many studies reported the prolonged negative effects of the COVID-19 pandemic on HCWs mental health in the first year [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported the prolonged negative effects of the COVID-19 pandemic on HCWs mental health in the first year [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies followed the progression of anxiety, depression, and stress among HCWs as the pandemic continued [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…56 Previous studies found that female healthcare workers tend to develop greater physical and emotional stress during COVID-19, and physicians had a higher resilience compared to nurses due to general medical knowledge, education, and training for swift respond to emergencies. [57][58][59][60] Therefore, physicians are better at dealing with poor social adaptation and feelings of isolation, which mitigates the HRPL.…”
Section: Discussionmentioning
confidence: 99%